Extracellular Vesicles From Osteotropic Breast Cancer Cells Affect Bone Resident Cells. (5th November 2019) - Loftus, Alexander; Cappariello, Alfredo; George, Christopher; Ucci, Argia; Shefferd, Kirsty; Green, Alice; Paone, Riccardo; Ponzetti, Marco; Delle Monache, Simona; Muraca, Maurizio; Teti, Anna; Rucci, Nadia
ABSTRACT: Extracellular vesicles (EVs) are emerging as mediators of a range of pathological processes, including cancer. However, their role in bone metastases has been poorly explored. We investigated EV‐mediated effects of osteotropic breast cancer cells (MDA‐MB‐231) on bone resident cells and endothelial cells. Pretreatment of osteoblasts with conditioned medium (CM) of MDA‐MB‐231 (MDA) cells promoted pro‐osteoclastogenic and pro‐angiogenic effects by osteoblast EVs (OB‐EVs), as well as an increase of RANKL‐positive OB‐EVs. Moreover, when treating osteoblasts with MDA‐EVs, we observed a reduction of their number, metabolic activity, and alkaline phosphatase (Alp) activity. MDA‐EVs also reduced transcription of Cyclin D1 and of the osteoblast‐differentiating genes, while enhancing the expression of the pro‐osteoclastogenic factors Rankl, Lcn2, Il1b, and Il6 . Interestingly, a cytokine array on CM from osteoblasts treated with MDA‐EVs showed an increase of the cytokines CCL3, CXCL2, Reg3G, and VEGF, while OPG and WISP1 were downregulated. MDA‐EVs contained mRNAs of genes involved in bone metabolism, as well as cytokines, including PDGF‐BB, CCL3, CCL27, VEGF, and Angiopoietin 2. In line with this profile, MDA‐EVs increased osteoclastogenesis and in vivo angiogenesis. Finally, intraperitoneal injection of MDA‐EVs in mice revealed their ability to reach the bone microenvironment and be integrated by osteoblasts and osteoclasts. In conclusion, we showed a role for osteoblast‐derived EVs and tumor cell–derived EVs in the deregulation of bone and endothelial cell physiology, thus fueling the vicious cycle induced by bone tumors. © 2019 American Society for Bone and Mineral Research.